Sustainable green chemistry - Benvenuto, Mark A. (Mark Anthony) (Green chemical processing ;, 2017)
"Sustainable Green Chemistry, the 1st volume of Green Chemical Processing, covers several key aspects of modern green processing. The scope of this volume goes beyond bio- and organic chemistry, highlighting the ecological and economic benefits of enhanced sustainability in such diverse fields as petrochemistry, metal production and wastewater treatment. The authors discuss recent progresses and challenges in the implementation of green chemical processes as well as their transfer from academia to industry and teaching at all levels. Selected successes in the greening of established processes and reactions are presented, including the use of switchable polarity solvents, actinide recovery using ionic liquids, and the removal of the ubiquitous bisphenol A molecule from effluent streams by phytodegradation" -- Publisher's description.